INTEGRITATE ȘI LIBERTATE DE CONȘTIINȚĂ ÎN PRAXIOLOGIA CREDO-BAPTISMALĂ (Journal for Freedom of Conscience (Jurnalul Libertății de Conștiință), 2022)
Integrity and Freedom of Conscience in Credo-Baptismal PraxiologyIn this article we will explore the way in wich community-validated baptismal praxiology is a true exercise of individual integrity and freedom. In credo-baptismal praxiology, the validity of the act itself is given by both the individual and the community, and baptism, in addition to the theological valences, also has an ethnographic dimension that cannot be overlooked. We will explore, for this reason, how the Early Church understood to relate to this universally accepted practice, but also how it has evolved over time. At the same time, we will briefly present the points of convergence as expressed in the document Baptism, Eucharist and Ministry, but also the reactions of some theologians regarding this document.